Pola Rekrutmen Politik Dalam Penentuan Kader Legislatif PDI Perjuangan di Kabupaten Belu - Petrus Gregorius Taek; Adeo Dato Januario Barros Mbiri (POLIGOVS, 2023)
The research aims to describe and explain the implementation of political party functions in the recruitment of cadres for the Indonesian Democratic Party of Struggle in Belu Regency to get votes in the 2024 elections, as well as widening the number of members with a recruitment mechanism that can be used as a mass basis for votes in facing the 2024 elections. This type of research uses the method qualitative to describe and explain the Implementation of Political Party Functions as PDIP Cadre Recruitment in Belu Regency. Data collection techniques use observation, interviews and documentation methods. Data analysis using interactive models. The results of the research show that the implementation of political party functions as recruitment for PDIP Belu party cadres means that PDIP Belu has an open recruitment pattern to produce cadres who have the potential to win the 2024 elections in Belu district.